Ball-milling synthesis of sulfonyl quinolines via coupling of haloquinolines with sulfonic acids. Issue 19 (27th July 2021) - Liu, Xiao-Wen; Wang, Jia-Qian; Ma, Hui; Zhu, Qi; Xie, Long-Yong
Abstract : A practical and environment-friendly methodology for the construction of sulfonyl quinolines through ball milling promoted coupling of haloquinolines with sulfonic acid under metal-, base-, solvent- and additive-free conditions was developed. Abstract : An efficient and practical approach for the synthesis of sulfonyl quinolines via ball milling promoted coupling of haloquinolines with sulfonic acid under metal-, solvent- and additive-free conditions has been developed. In contrast to the solvent-based sulfonylation reactions, this protocol has the advantage of shorter reaction time (10–20 min), mild reaction temperature, operational simplicity and excellent to quantitative yields, making this method very attractive for the preparation of sulfonyl quinoline compounds.